The hydrodynamical modeling of the Supernovae Ia explosion by means adaptive nested meshes on supercomputers - Kulikov, Igor; Chernykh, Igor; Protasov, Viktor (Journal of physics. Conference series, 2019)
The results of the study of an explosion point of supernova type Ia (SNIa) with using of mathematical modeling on supercomputers is given in the paper. Hydrodynamical model closed by the stellar equation of state and supplemented by Poisson equation for gravitational potential is used for modeling of a white dwarf. The nuclear combustion of carbon, for which the analytical solution is constructed, is accounted in the model. A multilevel organization of computations on nested grids is used in the solution. The new highorder accuracy numerical method based on the Godunov method, the Rusanov scheme and the piecewise parabolic method on local stencil, adapted for computations on nested grids, is built. The parallel implementation is based on the idea of distributed computations, where the architecture with shared memory is used for modeling of the hydrodynamic evolution of white dwarfs, when the critical values of temperature and density are reached, a new task is launched on the architecture with distributed memory, in which the evolution of hydrodynamic turbulence leading to supersonic nuclear combustion of carbon is simulated.